Anomalous origin of the long head of biceps in a patient with anterior shoulder instability and long-term results of its repair (Indian Journal of Case Reports, 2021)
The long head of the biceps tendon normally originates from the superior glenoid tubercle. There have been several descriptions of anomalous origins of the tendon of the biceps, but their clinical implications remain mostly unknown. They are mostly incidental findings during arthroscopic surgery and include aberrant origins and agenesis. Due to the rare nature of these lesions, it is unlikely that substantial sample size will be generated in the future to propose treatment recommendations. Nevertheless, shoulder arthroscopy surgeons should be aware of its potential to become pathologic and causing shoulder dysfunction. We are presenting a case of a young sportsperson who presented to us with a complaint of anterior instability and its long-term follow-up after repair. The anomalous origin of the biceps tendon was noted incidentally on arthroscopy while doing the repair though the patient did not report any pain due to the same both preoperatively and after surgery.